In Pursuit of Authenticity: Globalization and Nation Building in the Cayman Islands - Amit-Talai, Vered (Anthropologica, 2022)
Over the last decade, a number of publicly funded institutions have emerged in the Cayman Islands charged with the discovery, exploration and promotion of a Caymanian national identity and historical consciousness. They have emerged in the midst of a period of dramatic and very rapid economic transformation in which Cayman moved from a labour-exporting, small-scale maritime economy to become a major offshore financial as well as tourist centre, with increasing dependence on the inflow of foreign capital and imported skilled and professional contract labour. That dependence has produced both affluence and anxiety among many Caymanians about their ability to maintain a primary share of the opportunities arising in these new economic industries. The work of the cultural sector, while limited in popular appeal, has responded to these widespread anxieties by seeking to establish and reaffirm the status of one category of residents as rightful inheritors of Cayman and as such legitimately accorded special residential, electoral and employment entitlements. But it too has been dependent on the expertise, ideas and support of expatriate personnel and enthusiasts. In an important sense, Cayman has contracted out its nation building.